PENYEDIAAN FASILITAS PUBLIK DI KOTA TANJUNG SELOR SEBAGAI IBUKOTA PROVINSI KALIMANTAN UTARA - Dewi Rosanti; Adam Idris; Rita Kalalinggi (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
This study aims to know public perception towards public facilities in Tanjung Selor in regard to it’s status as the capital of North Borneo Province based on health facilities which include hospital facilities, health center facilities, North Borneo University Facilities, Local Parks Facilities, and Tourism Facilities. Informants in this study are the residents of Tanjung Selor. To obtain the data this study used observation, interview guidelines and documentation.This study uses descriptive qualitative data collection techniques based on the observation, interview, documentation.